Neurodegenerative effects of the cyanotoxin β-n-methylamino-l-alanine (BMAA) on retinal neurons - Soto, Tamara Belen (2017)
The non-proteic aminoacid BMAA is a cyanotoxin released by many cyanobacteria occurring in most dams and water resources around the world. Human chronic intake of this toxin has been linked with the development of neurodegenerative diseases, like Amyotrophic Lateral Sclerosis (ALS); Parkinson and Alzheimer Disease. Multiple studies have shown the effects of BMAA on live animals; however, its effects at the cellular or molecular levelsía are still mostly unknown. We here investigated the effects of BMAA on retinal amacrine and photoreceptor neurons and Muller glial cells (MGC) in vitro. We incubated pure neuronal cultures and mixed neuro-glial cultures obtained from newborn rat retinas, with 400 nM BMAA for 2 days. We then evaluated cell death and apoptosis by Propidium Iodide (PI) TUNEL assays, and DAPI staining. Mitochondrial activity was assessed by using Mitotracker and cytoskeleton integrity and axonal outgrowth were analyzed by immunocytochemical methods. In `pure neuronal cultures, BMAA increased the percentage of apoptotic amacrine and photoreceptor neurons, from 21.6% to 64.5% and from 29.3% to 65.7%, respectively, in controls and BMAA-treated cultures. Noteworthy, functional mitochondria decreased from 55% to 35% in photoreceptors but only slightly in amacrine neurons. In addition, BMAA treatment disrupted the organized assembly of tubulin in axons. BMAA addition to mixed neuro-glial cultures induced lamellipodia retraction and loss of mitochondrial membrane potential in MGC, but did not increase their cell death. Moreover, MGC partially prevented neuronal death. These results suggest that BMAA induces subcellular changes in both neurons and glial cells, and markedly affects the viability of retinal neurons, confirming its threat to human health as a potential inducer of neurodegenerative damages.